2016
DOI: 10.1093/ntr/ntw166
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatic and Sympathetic Attitudes Toward Cancer Patients Who Smoke: A Qualitative Analysis of an Online Discussion Board Forum

Abstract: This study helps raise awareness of stigma toward cancer patients who smoke and provides insight into the processes that may influence stigmatic as compared to sympathetic attitudes toward these patients. Results suggest that population-based strategies to educate the public regarding the nature of nicotine addiction, difficulty of quitting, and benefits of quitting for cancer patients may be useful for reducing stigma against cancer patients with a smoking history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 83 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…115 Marlow et al 116 randomized a non-patient sample to complete a cancer stigma scale related to lung, colorectal, skin, breast, or cervical cancer and found that participants reported the greatest levels of stigma related to lung cancer, with increased perceptions of responsibility for their disease. In another unique study, Luberto et al 117 , used grounded theory to analyze online comments about a study detailing smoking among lung and colorectal cancer patients. Stigma-based comments were common, with discussions centering on blame and personal responsibility for lung cancer.…”
Section: A Societal Perspective To Addressing Lung Cancer Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…115 Marlow et al 116 randomized a non-patient sample to complete a cancer stigma scale related to lung, colorectal, skin, breast, or cervical cancer and found that participants reported the greatest levels of stigma related to lung cancer, with increased perceptions of responsibility for their disease. In another unique study, Luberto et al 117 , used grounded theory to analyze online comments about a study detailing smoking among lung and colorectal cancer patients. Stigma-based comments were common, with discussions centering on blame and personal responsibility for lung cancer.…”
Section: A Societal Perspective To Addressing Lung Cancer Stigmamentioning
confidence: 99%
“…Stigma-based comments were common, with discussions centering on blame and personal responsibility for lung cancer. 117 In terms of public attention and action, Weiss et al 118 conducted a phone survey of 1,071 people and asked about their likelihood to donate money or volunteer time for a cancer organization; 29% of respondents stated that they were “likely or very likely to donate time/money in the future” to breast cancer organization compared to 18% of respondents for a lung cancer organization. Similarly, 25% of respondents picked breast cancer out of all other cancer types as an organization to support in the future as opposed to 12% for lung cancer support.…”
Section: A Societal Perspective To Addressing Lung Cancer Stigmamentioning
confidence: 99%
“…Nicotine, as well as its structural analogues nitrosamines 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone and N'-nitrosonornicotine, can activate a variety of nAChR subtypes found in the parasympathetic nervous system, resulting in a various biological responses (40). Nicotine can induce the proliferation of a variety of cancer cells, such as small cell lung cancer, non-small cell lung cancer, pancreatic and colon cancer cells, in receptor-dependent manner (41,42). In human bronchial epithelial cells and lung cancer cells, the α7nAChR inhibitors mecamylamine reduced cell proliferation mediated by nicotine (43).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to other types of cancer, lung cancer is the most stigmatised due to strong associations with smoking tobacco and perceptions that the individual holds responsibility for their disease (Chapple et al, 2004;Knapp et al, 2014;Knapp-Oliver and Moyer, 2012;Luberto et al, 2016Marlow et al, 2010, 2015. A survey of attitudes towards cancer found that respondents considered lung cancer patients to be much more responsible for their illness than other cancer types (Marlow et al, 2015).…”
Section: Current Studymentioning
confidence: 99%
“…Similarly, a qualitative study of 45 lung cancer patients found that many patients, whether smokers or not, felt unjustly blamed for their illness which deterred them from seeking support from friends, family and health professionals (Chapple et al, 2004). Also, a qualitative analysis of an online discussion board found that individuals with no personal experience with cancer or smoking, particularly stigmatised lung cancer patients (Luberto et al, 2016). This stigmatisation of lung cancer also affects public support and funding.…”
Section: Current Studymentioning
confidence: 99%